Study protocol for the EYEdentify project: An examination of gaze behaviour in autistic adults using a virtual reality-based paradigm - Alberte Cathrine Ehrhardt Jeppesen; Johannes Andresen; Rizwan Parvaiz; Lars Clemmensen; Jens Richardt Møllegaard Jepsen; Dan Witzner Hansen; Louise Birkedal Glenthøj (PLoS ONE, 2025)
Introduction Autism Spectrum Condition (ASC) is characterised by difficulties in social communication and interaction, which may pose significant challenges to daily functioning throughout life. While current diagnostic methods for ASC often rely on measures based on subjective reports, there is a growing need for objective, quantifiable measures to support current clinical assessment of ASC. Eye-tracking technology records eye and gaze movements in real time and provides a direct and objective method for assessing social attention. Integrating eye-tracking within virtual reality (VR) environments presents a novel approach for capturing gaze behaviour in dynamic, ecologically valid social scenarios. This study aims to investigate whether VR-based eye information can reveal group differences in gaze behaviour between autistic adults and neurotypical controls in simulated social interactions. Methods This case-control study will include 140 adults diagnosed with ASC and 50 neurotypical controls, matched by age and gender. Participants will engage in six VR-based social scenarios, which vary in social complexity and the presence of non-social distractors. Eye information will be measured using eye-tracking technology integrated into a head-mounted display. Gaze behaviour will be analysed through fixation-based metrics on parameters including number of fixations, mean fixation time, and dwell time, on predetermined Areas of Interest. Analysis Statistical analyses will assess between-group differences in gaze behaviour as well as correlations between gaze metrics and clinical measures of social functioning, social cognition and symptom severity. Discussion This study utilises VR-based eye-tracking to investigate novel paradigms for assessing gaze behaviour in ASC in immersive, interactive environments and aims to advance the current understanding of visual social attention in ASC. Positive outcomes from this study may support further research into VR-based eye-tracking to supplement existing clinical assessment methods.